Early Post-stroke Depression and Mortality: Meta-Analysis and Meta-Regression - Bartoli, Francesco; Di Brita, Carmen; Crocamo, Cristina; Clerici, Massimo; Carrà, Giuseppe (Frontiers in Psychiatry, 2018)
Background: Post-stroke depression (PSD) is a common and serious complication after stroke. In this systematic review and meta-analysis, we evaluated the association between early PSD and mortality, considering depressive symptoms occurring within the first 3 months after the neurological event. Methods: This meta-analysis was conducted following Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines and based on studies indexed till May 2018 in PubMed and Web of Science databases. The relative risk (RR) for mortality in individuals with PSD, as compared with non-depressed ones, was estimated. Findings were pooled according to a random-effects model. Meta-regression and subgroup analyses were carried out. Results: We included seven studies, accounting for 119,075 individuals, of whom 17,609 suffering from an early PSD. We found higher rates of mortality in subjects with PSD as compared with non-depressed ones (RR = 1.50; 95%CI: 1.28 to 1.75; p < 0.001). Heterogeneity across studies was moderate (I2 = 50.7%). Subgroup analysis showed a slightly higher effect of PSD on short-term mortality (RR = 1.70; p < 0.001), as compared with long-term one (RR = 1.35; p = 0.01). According to relevant meta-regression analyses, the estimate was influenced by sample proportion of men (p = 0.043). Conclusions: Despite some limitations, our study shows the negative impact of early PSD on survival rates. Mechanisms underlying this association still need to be elucidated and several interpretations can be hypothesized. Future research should test if an early management of depression may increase life expectancy after stroke.